PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VII - Latifah, Adinda Aulia (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematical communication ability is one of the abilities that must have by students to support the learning process. But in fact, the mathematical ability of students in class VII MTsN 6 Kota Padang is still relatively low. One effort that is believed to be able to solve this problem is using Think Talk Write cooperative learning model. This kind of research is a quasi-experiment using a static group design. The sample was determined using the simple random sampling technique. The instruments used are quizzes and mathematical communication tests. Then, hypothesis testing using the T-test.  Data analysis shows that P-value is 0,000 which means refuse. Because of that, it can be concluded that the communication ability of students in class VII MTsN 6 Kota Padang was taught by using the Think Talk Write model better than by using conventional learning. Keywords. – Mathematical Communication Abilities, Cooperative Learning, Think Talk Write